Cigarette smoking in adolescents with type 1 diabetes mellitus and congenital adrenal hyperplasia - Pelin Asfuroğlu; Aslıhan Araslı-Yılmaz; Zehra Aycan (The Turkish Journal of Pediatrics)
Adolescence is a long period involving many physical and psycho-social changes experienced during transition from childhood to adulthood. In this period, behaviors such as curiosity and risk-taking are common, and cigarette smoking initiation is one of those behaviors. In this study, it was aimed to find out whether chronic diseases are an effective factor or not in the cigarette smoking initiation of adolescents. One-hundred adolescents with Type 1 Diabetes Mellitus (T1DM) and 50 adolescents with Congenital Adrenal Hyperplasia (CAH) aged 12 and above under follow-up at the Pediatric Endocrinology Clinic and 100 healthy adolescents within the same age group who applied to the Adolescent Outpatient Clinic were included in the study. A survey was applied to all of these adolescents, which had been developed by researchers and contained questions about their socio-demographic features and cigarette smoking. Fourteen (5.6%) of the 250 adolescents were smokers. The rate of those who tried, but quitted cigarette smoking was found as approximately 20%. Cigarette smoking rate of those with T1DM was 1%, of those with CAH was 4%, and of the healthy adolescents was 11%. Cigarette smoking was significantly lower in those with a chronic disease (2%) than those who were healthy (11%). Adolescents` parents and friends had an effect on the cigarette smoking initiation, and adolescents smoked their first cigarette generally because of curiosity. It was seen in this study that the adolescents with a chronic disease less frequently smoked cigarettes than the healthy adolescents, the rate of cigarette smoking in parents of cigarette smoking adolescents was very high, and their parents and friends had an effect on cigarette smoking initiation of adolescents.